2019
DOI: 10.1002/gepi.22198
|View full text |Cite
|
Sign up to set email alerts
|

A network approach to prioritizing susceptibility genes for genome‐wide association studies

Abstract: The heritability of complex diseases including cancer is often attributed to multiple interacting genetic alterations. Such a non‐linear, non‐additive gene–gene interaction effect, that is, epistasis, renders univariable analysis methods ineffective for genome‐wide association studies. In recent years, network science has seen increasing applications in modeling epistasis to characterize the complex relationships between a large number of genetic variations and the phenotypic outcome. In this study, by constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 80 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…Studies using benchmarking comparisons with several models offer a form of standardization for selection, contributing to research transparency which is crucial for work justifying investment in functional study. Recent studies are more frequently incorporating benchmarking comparison showing the development of robust methodology in this field (Isakov et al, 2017;Kafaie et al, 2019;Vitsios and Petrovski, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies using benchmarking comparisons with several models offer a form of standardization for selection, contributing to research transparency which is crucial for work justifying investment in functional study. Recent studies are more frequently incorporating benchmarking comparison showing the development of robust methodology in this field (Isakov et al, 2017;Kafaie et al, 2019;Vitsios and Petrovski, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These results were also supported by comparison with a combined framework using all models in prioritization, the stacking classifier, ensuring the highest reliability in the chosen classifier for each disease (Vitsios and Petrovski, 2019). Kafaie et al (2019) aimed to prioritize genes associated with colorectal cancer comparing various models (SVM, random forest, logistic regression with stochastic gradient descent, and K−nearest neighbors). They found that logistic regression was the highest performing ML model -emphasizing that a classification problem may require simpler solutions.…”
Section: Machine Learning Modelsmentioning
confidence: 93%
See 3 more Smart Citations